Drift oscillations supperssion during the electron plasma decay - Tarasov, M.I.; Tarasov, I.K.; Volkov, E.D. (Вопросы атомной науки и техники, 2008)
The drift waves were excited in non-neutral electron plasma created by injection of a hot electron beam into the drift chamber of the experimental device. The main attention is paid to the regime in which the injected electrons are captured and confined in the central area of the drift chamber in a metastable state. The duration of such confinement was anomalously long. Earlier such state was explained by the presence of coherent drift oscillations in the plasma of the confined particles. But a set of experiments with the drift oscillation suppression have shown that the metastable state of confined plasma exists without a drift oscillations generation. An effective method of the drift wave suppression was found.